2011
DOI: 10.1186/1754-6834-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical distribution of lignin and hydroxycinnamic acids in sugar-cane cell walls and its correlation with the enzymatic hydrolysis of polysaccharides

Abstract: BackgroundLignin and hemicelluloses are the major components limiting enzyme infiltration into cell walls. Determination of the topochemical distribution of lignin and aromatics in sugar cane might provide important data on the recalcitrance of specific cells. We used cellular ultraviolet (UV) microspectrophotometry (UMSP) to topochemically detect lignin and hydroxycinnamic acids in individual fiber, vessel and parenchyma cell walls of untreated and chlorite-treated sugar cane. Internodes, presenting typical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0
20

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 31 publications
9
68
0
20
Order By: Relevance
“…These authors suggested that, compared with the rind, a less lignified pith would favor cell wall degradability by increasing the accessible and potentially degradable area. Similarly, Siqueira et al (2011) observed that sugarcane pith samples were promptly hydrolyzed by cellulases, while the conversion of cellulose in rind samples was dependent on chlorite pretreatments. The significantly higher cell wall recalcitrance of sugarcane rind samples was mainly attributed to the massive presence of lignin-rich fibers and vessels, but the presence of a more condensed G-rich lignin in this anatomical region (this study) of the stem might also be implicated.…”
Section: Discussionmentioning
confidence: 94%
“…These authors suggested that, compared with the rind, a less lignified pith would favor cell wall degradability by increasing the accessible and potentially degradable area. Similarly, Siqueira et al (2011) observed that sugarcane pith samples were promptly hydrolyzed by cellulases, while the conversion of cellulose in rind samples was dependent on chlorite pretreatments. The significantly higher cell wall recalcitrance of sugarcane rind samples was mainly attributed to the massive presence of lignin-rich fibers and vessels, but the presence of a more condensed G-rich lignin in this anatomical region (this study) of the stem might also be implicated.…”
Section: Discussionmentioning
confidence: 94%
“…However, visual characterizations of cellular components elucidating the hemicellulose degradation and delocalization of lignin after oxalic acid fiber expansion (OAFEX) pretreatment have yet to be performed. Cell wall anatomy of SB and macroscopic/microscopic barriers for cellulase-mediated saccharification reveal that cell wall hydrolysis encompasses several orders of magnitude (10 0 -10 -9 meters [9,10]. Oxalic acid (OA) is a strong dicarboxylic acid with higher catalytic efficiency than the sulfuric acid, and acts primarily upon hemicellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Essa região é composta principalmente por feixes vasculares, formados por vasos (xilema e floema), circundados por fibras. Os feixes vasculares transportam seiva e são responsáveis pela sustentação (MOORE, 1987 Além disso, as células do córtex são mais lignificadas que as células de medula (SIQUEIRA et al, 2011;ZENG et al, 2012). Como consequência dessa maior lignificação, as células de córtex são mais recalcitrantes, oferecendo maior resistência à desconstrução enzimática, discutida mais adiante.…”
Section: Parede Celular Da Cana-de-açúcarunclassified
“…Além desses substituintes, grupos acetila e ácidos hidroxicinâmicos (ferúlico e cumárico) também são encontrados (WENDE; FRY, 1997). (LEE et al, 2009;SIQUEIRA et al, 2011SIQUEIRA et al, , 2013 (KANG et al, 2013;SANTOS et al, 2011;TOQUERO;BOLADO, 2014).…”
Section: Parede Celular Da Cana-de-açúcarunclassified